2022
DOI: 10.3390/brainsci12121732
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Alleviates Neuroinflammation by Inhibiting the HMGB1 Signaling Pathway in Rats with Sepsis-Associated Encephalopathy

Abstract: Sepsis-Associated Encephalopathy (SAE) is common in sepsis patients, with high mortality rates. It is believed that neuroinflammation is an important mechanism involved in SAE. High mobility group box 1 protein (HMGB1), as a late pro-inflammatory factor, is significantly increased during sepsis in different brain regions, including the hippocampus. HMGB1 causes neuroinflammation and cognitive impairment through direct binding to advanced glycation end products (RAGE) and Toll-like receptor 4 (TLR4). Electroacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Cognitive performance was then evaluated using the Y-maze test to assess working memory 26 and the NOR/NLR behavioral test for learning and recognition memory. 27 During the Y-maze assay, the percentage of alternation was significantly lower in the Citro/Veh mouse group than in the non-infected NI/Veh mouse group ( Figure 5d ).…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive performance was then evaluated using the Y-maze test to assess working memory 26 and the NOR/NLR behavioral test for learning and recognition memory. 27 During the Y-maze assay, the percentage of alternation was significantly lower in the Citro/Veh mouse group than in the non-infected NI/Veh mouse group ( Figure 5d ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have proven the significant neuroprotective effect of the widely used acupoints ST36 and GV20 in the management of neurological diseases 35–37 . Specifically, the ST36 has proven to be beneficial in alleviating chronic pain 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven the significant neuroprotective effect of the widely used acupoints ST36 and GV20 in the management of neurological diseases. 35 , 36 , 37 Specifically, the ST36 has proven to be beneficial in alleviating chronic pain. 38 Consistent with previous findings, we found that EA stimulation acupoints at ST36 and GV20 markedly decreased pain hypersensitization induced by CCI surgery, with the anti‐nociceptive effect increased in a time‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%